9.3.2 The Use of Models across the Contractual Boundary: Past, Present and Future. Issue 1 (July 2014) - Do, Quoc; Cook, Stephen; Fossnes, Terje; Haskins, Cecilia
Abstract Model‐Based Systems Engineering (MBSE) practices have been gathering momentum for over 20 years and are seen as the future of systems engineering. MBSE formalises the practice of systems engineering through the use of models and its aim is to overcome the limitations inherent in describing complex systems and their development and sustainment using documents. However, certain project practices, in particular the tendering and contracting processes, are still strongly tied to the use of documents. This paper identifies the challenges that need to be addressed to use MBSE across the contractual interface in a competitive tendering environment. The focus is on the transition of models created by the customer (acquirer) during the capability definition phase to the supplier both during the tendering process and through the systems architectural design and development phases. The paper unfolds with a literature survey and then progresses to surface key insights and challenges for the adoption of model‐centric acquisition, looking into the past, present and future from the Australian and Norwegian defence perspectives. This is supplemented through case studies involving the utilisation of RDD‐100 for model‐centric acquisition of Frigates by the Royal Norwegian Navy and through ongoing research by the Australian Defence Science and Technology Organisation, and the Defence and Systems Innovation Centre. The paper concludes with a summary of the achievements to date and the challenges to be addressed in order to enable and foster the widespread adoption of model‐centric tendering and equipment acquisition.